Analysis of Junior High School Students Creative Thinking Skills in Distance Learning - Nisa Auliyah; Elok Sudibyo; Munasir (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Purpose of this study is to analyze the creative thinking skills of junior high school students in physics in distance learning. This study describes students' creative thinking skills in physics using question instruments related to creative thinking. The method used in this research is descriptive quantitative method. The test is conducted online via google form. The instrument contains eight questions related to the physical matter of substance pressure and its application in everyday life. The subjects of this study were 32 students of VIII Junior High School in Gresik. The results showed that the analysis related to students creative thinking ability in physics obtained an average of 51.5% which was included in the creative enough category. On the fluency indicator it was 37% with the less creative category, 58% on the flexible thinking indicator (Flexibility). with the creative enough category, 64% on the original thinking indicator (Originality) with the creative category, 53% on the detailed thinking indicator (Elaboration) with the creative enough category and 43% on the metaphorical thinking indicator (metaphorical thinking) with the creative enough category. From these results it can be concluded that the creative thinking skills of student’s physics in distance learning are still in the sufficient category so that it needs to be improved especially in distance learning at this time, so that alternatives are needed in learning that is suitable for distance learning. Creative thinking skills are one of the important skills to be trained in the 21st century today.